Tindak Tutur dalam Tayangan Kanal Youtube WAW Entertaiment - Pratiwi, Dyah (Dinamika: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2023)
The development of the times makes the media for communication become increasingly widespread. This also affects speech acts both orally and in writing. Oral speech can be found on social media. This article will describe the speech acts of locutionary, illocutionary, and perlocutionary in the WAW Entertainment YouTube channel, episode "Isyana Pancing Endy So That You Know the Ideal Boy Type". The method used is descriptive. The research data is in the form of utterances conveyed by speakers. Data was collected using literature study (documentary) techniques related to types of speech acts. The results of the research show that the utterances of the loan in Youtobe, specifically the episode, consist of assertive, directive, and expressive illocutionary speech acts. The dominating illocutionary act is the directive illocutionary, while the least is an assertive illocutionary act.Keywords: illocutionary; locution; perlocutionary; pragmatics; speech actPerkembangan zaman menjadikan media untuk berkomunikasi menjadi semakin luas. Hal ini juga berpengaruh terhadap tindak tutur baik lisan maupun tulis. Tuturan lisan bisa ditemukan di media sosial. Artikel ini akan mendeskripsikan tindak tutur lokusi, ilokusi, dan perlokusi dalam tayangan kanal YouTube WAW Entertaiment, episode â€œIsyana Pancing Endy Supaya Kasih Tau Tipe Cowok Idealâ€. Metode yang digunakan yaitu deskriptif. Data penelitian berupa tuturan-tuturan yang disampaikan oleh penutur. Data dihimpun menggunakan teknik studi pustaka (dokumenter) berkaitan dengan jenis-jenis tindak tutur. Hasil penelitian menunjukkan bahwa tuturan losan dalam Youtobe, khusus episod itu terdiri dari tindak tutur ilokusi asertif, direktif, dan ekspresif. Tindak tutur ilokusi yang mendominasi ialah ilokusi direktif, sedangkan yang paling sedikit adalah ilokusi asertif.Kata kunci: ilokusi; lokusi; perlokusi; pragmatic; tindak tutur